Boron neutron capture therapy for head and neck cancer: Relevance of nuclear-cytoplasmic volume ratio and anti-tumor effect. -A preliminary report - Aihara, Teruhito; Hiratsuka, Junichi; Kamitani, Nobuhiko; Nishimura, Hirotake; Ono, Koji (Applied radiation and isotopes, 2020)
BNCT is a type of particle beam radiation therapy that utilizes an α particle and 7Li nucleus generated when a thermal neutron is captured by a 10B nucleus involved in the boron compound that has been taken up into tumor tissue selectively. In this report, the relevance of N/C ratio of tumor cell and anti-tumor effect for BNCT clinical cases of head and neck cancer were verified. Examination of pre-irradiated tumor histopathological specimens of 9 BNCT treated head and neck cancer patients (4 CR patients, 5 non-CR patients) was performed. The statistically significant difference between the CR group and the non-CR group was examined for the physical dose was multiplied by the absolute biological effectiveness (ABE) value determined from the patient's tumor specific N/C ratio. Analysis showed the mean tumor dose could not distinguish between CR and non-CR groups. However, the ABE dose could clearly distinguish between the CR group and the non-CR group (p = 0.0250). The N/C ratio of tumor cell can influence the anti-tumor effect of BNCT for HNC. 1.This study is relevance of N/C ratio and anti-tumor effect for BNCT.2.9 patients (4 CR patients, 5 non-CR patients) in our institution who underwent BNCT were analyzed.3.The statistically significant difference between the CR and the non-CR was examined for ABE dose.4.The ABE dose could clearly distinguish between the CR group and the non-CR group (p = 0.0250).5.The ABE dose can influence the anti-tumor effect of BNCT for HNC.